Differences in dissolved organic matter and analysis of influencing factors between plantations pure and mixed forest soils in the loess plateau - Meng, Yongxia; Li, Peng; Xiao, Lie; Hu, Bingze; Zhang, Chaoya; Yang, Shutong; Liu, Jialiang; Zhao, Binhua (Frontiers in Forests and Global Change, 2024)
The dissolved organic matter (DOM) in forest ecosystems significantly impacts soil carbon cycling due to its active turnover characteristics. However, whether different plantation forest soil profiles exhibit distinct DOM characteristics remains unclear. Hence, utilizing fluorescence spectroscopy and the parallel factor analysis (PARAFAC) method, a 1-meter soil profile analysis was carried out on three distinct artificial forests (Pinus tabuliformis (PT), Quercus crispula (QC), and a mixed forest of PT and QC (MF)), concurrently assessing the impact of soil chemical properties and enzyme activity on dissolved organic matter (DOM). The findings indicated that the mean concentration of dissolved organic carbon (DOC) was greatest in the MF and lowest in PT, exhibiting considerable variation with soil depth, suggesting that mixed tree species may promote the discharge of organic matter. The fluorescence spectra revealed two distinct peaks: humic-like fluorescence peaks (Peaks A and C) and a protein-like fluorescence peak (Peak T), with the most intense fluorescence observed in MF soil. As the soil depth increased, the fluorescence intensity of Peaks A and C steadily declined, while the intensity of Peak T rose. Four DOM components were identified in three types of plantations forests: surface soil was dominated by humic acid-like fluorescent components (C1 and C2), while the deep soil was primarily characterized by protein-like fluorescence components (C3 and C4). Different soil profile fluorescence parameter indices indicated that the source of DOM in the surface soil (i.e., 0–20 cm) was mainly allochthonous inputs, whereas, in the deep soil (i.e., 60–100 cm), it was mainly autochthonous, such as microbial activity. The findings from the partial least squares path modeling (PLS-PM) revealed that TP, aP, NH4+-N, and the combined impact of soil enzymes were influential in shaping the diversity of DOM attributes. Put differently, alterations in DOM concentration were concomitantly influenced by forest classification, soil characteristics, and depth. It has been demonstrated that, in contrast to monoculture forests, the establishment of mixed forest models has been more advantageous in enhancing the soil dissolved organic matter (DOM). These discoveries offer innovative perspectives on the dynamic characteristics of DOM in soil profiles and its influencing factors under different plantations forest planting patterns.